Thugs rje chen po Padma dri med dkar po las Mnaʼ sdig bśags pa ṅan soṅ kun ʼjoms : a Vajrayana Buddhist formula of confession and atonement from the Padma dri med padma dkar po cycle ([s.n.], 1968)
Rediscovered ritual of the Nyingmapa tradition.